The determinant factors of green practices adoption for logistics companies in Malaysia. a case study of PKT Logistics Group Sdn. Bhd. / Irwan Ibrahim ... [et al.] - Ibrahim, Irwan; Sundram, Veera Pandiyan Kaliani; Omar, Emi Normalina; Yusoff, Najmuddin; Amer, Afizan (Universit Teknologi MARA Cawangan Selangor, 2019)
This study examines factors that influence the intention to adopt green practices for logistics companies. The determinant factors include technological, organizational, environmental and environmental awareness. The data came from the questionnaire survey on logistics companies in Malaysia, and 150 samples were analyzed. The survey results reveal that three of the factors show insignificant result towards green practices adoption while one factor has positive influences on the intention to adopt green practices. Technological, environment and environment awareness factors exhibit insignificant influences on the willingness to adopt green practices while the organizational factors exhibit significant influences on the willingness to adopt green practices